Demanding Progressive Judges' Decisions for Fulfillment of Justice for Disputing Parties - Wantu, Fence M; Puluhulawa, Irlan (JURNAL LEGALITAS, 2023)
Basically, judges are the main actors organizing judicial power and at the same time as guardians of justice for litigants. Judge decisions that reflect law and justice simultaneously are not easy to realize. The objectives of this study are 1). To find out and analyze the development of progressive legal teachings through judges' decisions in court. 2). To find out and analyze the teachings of progressive law through judges' decisions and their influence on justice. The research method used is normative. The approaches taken are as follows: a). statute approach. b). Conceptual approach. c). Case approach. The sources of legal materials used consist of primary legal materials, secondary legal materials and tertiary legal materials. While the analysis used in this research is descriptive technique and comparative technique. The conclusions of this research are 1). The development of progressive legal teachings through judges' decisions in court is a must and cannot be negotiated anymore. 2). That the teachings of progressive law through judges' decisions and their influence on justice to answer the demands of the times today that judges' decisions are no longer only identical to the written legal rules contained in the law as taught by positivism, but judges' decisions are as much as possible able to provide welfare for the parties to the dispute and justice seekers and society in general.